Natural Resources, Inequality and Conflict - Ali, Hamid E.; Cederman, Lars-Erik. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This edited volume explores the link between natural resources and civil conflict, focusing especially on protest and violence in the context of mining and the extraction of minerals. The primary goal of the book is to analyze how the conflict-inducing effect of natural resources is mediated by inequality and grievances. Given the topicality of the current boom in mining, the main empirical focus is on non-fuel minerals. The volume is structured in four parts. Part I sets the stage of the volume in two chapters. Part II contains large-N studies of fuel and non-fuel resources and their effect on conflict. Based on qualitative methods, Part III presents case studies focusing on Zambia, India, Guatemala and Burkina Faso, which investigate the mechanisms between the extraction of natural resources and violent conflict. Finally, Part IV provides a summary of the previous analyses. Hamid E. Ali is Associate Professor of Economics and Public Policy, Doha Institute for Graduate Studies, Qatar, and the author of Darfur Political Economy: A Quest for Development (2014), nd co-author with Christos Kollias of Defense Spending, Natural Resources, and Conflict (2017). He is also the author and co-author of articles in many scholarly journals. Lars-Erik Cederman is Professor of International Conflict Research at ETH Zürich, Switzerland, and the author of Emergent Actors in World Politics: How States and Nations Develop and Dissolve (1997) and co-author of Inequality, Grievances and Civil War (2013), as well as numerous articles in scientific journals.
1. Introduction -- 2. Mineral Resources and Conflict: An Analytical Overview -- 3. No Extraction without Representation: The Ethno-Regional Oil Curse and Secessionist Conflict -- 4. Digging Deeper: On the Role of Grievances in African Mining Conflicts -- 5. Ethnic Mobilization and Collective Grievances in the Cooper Mining Areas of Zambia -- 6. Resource Extraction and Conflict in India -- 7. Indigenous Mobilization and Resource Extraction in Guatemala -- 8. Fueling Conflicts by Sharing Benefits? Qualitative Evidence from a Mining Conflict in Burkina Faso -- 9. Conclusions for Theory and Policy.
Keywords: Economic development; Development Studies; Development Studies; Development Studies